OP0104 Bone Quality, as Measured by Trabecular Bone Score, in Female Postmenopausal Patients with Systemic Sclerosis and Rheumatoid Arthritis. (15th July 2016) - Casabella, A.; Seriolo, C.; Botticella, G.; Molfetta, L.
Abstract : Background: Patients affected by Systemic Sclerosis (SSc) and Rheumatoid Arthritis (RA) might present an increased risk of low bone mass as a result of multisystemic disorder including treatment, low vitamin D levels and physical inactivity[1] . Trabecular Bone Score (TBS) is an index extracted from the dual-energy X-ray absorptiometry (DXA) that provides an indirect measurement of bone axial microarchitecture and allows to get informations about bone quality[2] . Objectives: The aim of this study was to assess bone quality in SSc patients using TBS in comparison with a "high-risk" population with RA. Methods: 74 patients (mean age 65±9 years) affected by SSc, 98 RA patients (mean age 61±8 years) and 60 age-matched healthy controls (mean age 64±11 years) were studied. Bone Mineral Density (BMD, g/cm 2 ) of the lumbar spine (L1-L4) was analyzed using DXA scan (Lunar Prodigy). Lumbar spine TBS was derived for each spine DXA examination blinded to clinical parameters and outcomes using TBS iNsight Medimaps (Lunar Prodigy). TBS value >1.350 is considered normal whereas TBS value <1.200 indicates a degraded bone microarchitecture. Results: Out of 74 enrolled patients with SSc, 56 (76%) presented bone loss; in particular 32 (43%) showed osteoporosis and 24 (32%) osteopenia. In RA patients bone loss was observed in 78 patients (80%); in particular 52 osteoporosis (53%) and 41 (42%) osteopenia. BMD was found significantly lower in SSc and RA patients compared with matched control group (respectively, Lumbar spine: 0.998±0.161 g/cm 2 and 0.862±0.194 g/cm 2 vs 1.240±0.932 g/cm 2 ; Femoral neck: 0.784±0.212 g/cm 2 and 0.668±0.141 g/cm 2 vs 0.845±0.164 g/cm 2 ; Ward 0.563±0.173 g/cm 2 and 0.486±0.221 g/cm 2 vs 0.657±0.106 g/cm 2 ; Trochanter: 0.666 ±0.104 g/cm 2 and 0.598±0.231 g/cm 2 vs 0.725±0.143 g/cm 2 ; Total hip: 0.827±0.182 g/cm 2 and 0.764±0.244 g/cm 2 vs 1.033±0.161 g/cm 2, all p<0.001). Lumbar spine TBS was found significantly lower in SSc and RA patients compared with matched control group (respectively, 1.032±0.163 and 0.904±0.148 vs 1.361±0.126, both p<0.001). There was no significant difference in mean lumbar spine TBS between patients with SSc and RA (p=0.238). Conclusions: This detailed study shows a decreased BMD and TBS values in SSc and RA patients when compared to healthy controls. In addition TBS, evaluated at the lumbar spine, with lumbar and femoral BMD, could discriminate patients with alterated bone microstructure and could become a new clinical tool in the general diagnosis of osteoporosis in inflammatory rheumatic diseases, such as SSc and RA. References: Cutolo M et al. Autoimmun Rev 2011:12;84–7 Roux JP et al. Osteoporosis Int 2013; 24(9):2455–60. Disclosure of Interest: None declared